A human monoclonal antibody isolated from Japanese encephalitis virus vaccine-vaccinated volunteer neutralizing various flaviviruses - Dong Chen; Dong Chen; Dong Chen; Jiayi Zhang; Jiayi Zhang; Jiayi Zhang; Yusha Liu; Jiayang Zhu; Jie Chen; Hongxia Ni; Jinsheng Wen (Frontiers in Microbiology)
IntroductionJapanese encephalitis virus (JEV) and Zika virus (ZIKV) are prevalent in over 80 countries or territories worldwide, causing hundreds of thousands of cases annually. But currently there is a lack of specific antiviral agents and effective vaccines.MethodsIn the present study, to identify human neutralizing monoclonal antibody (mAb) against JEV or/and ZIKV, we isolated ZIKV-E protein-binding B cells from the peripheral venous blood of a healthy volunteer who had received the JEV live-attenuated vaccine and performed 10× Genomics transcriptome sequencing and BCR sequencing analysis, we then obtained the V region amino acid sequences of a novel mAb LZY3412. We expressed mAb LZY3412 and evaluated its ability to bind to E proteins of dengue virus, JEV and ZIKV, neutralize JEV and ZIKV infections in vitro, protect mice against lethal JEV or ZIKV attack. The epitopes on E proteins of JEV/ZIKV recognized by mAb LZY3412 were analyzed using molecular docking and constructing E protein mutants.ResultsOur results show that recombinant mAb LZY3412 has high-affinity with the E proteins of three viruses, with the kinetically derived binding affinity (KD) values of 440 and 482.5 nM against JEV-E protein and ZIKV-E protein, respectively; recombinant mAb LZY3412 can efficiently neutralize JEV and ZIKV infections in vitro, with the NT50 values of 19.9 ng/mL and 631 ng/mL, respectively; application of recombinant mAb LZY3412 can significantly improve the percentage survival and reduce the serum viral loads of neonatal mice infected with JEV or ZIKV. Finally, two amino acid residues (Ala399 and Gly400) located in EDIII of JEV-E protein were potentially recognized by LZY3412 whereas two amino acid residues (Met15 and Thr406) out of EDIII of ZIKV-E proteins were recognized by LZY3412.DiscussionConsidering mAb LZY3412 has neutralizing effects on various flaviviruses, this mAb is expected to be developed as therapeutic or preventive drug for these flaviviruses, and can also be used to guide the development of vaccines against these flaviviruses.